RELIGIOUS AND SOCIO-PSYCHOLOGICAL DETERMINANTS OF MANAGERIAL DECISION MAKING (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article examines religious and socio-psychological factors that influence the management decision-making process of managers. Various aspects such as worldview, moral attitudes and pressure group are analyzed, as well as their significance for management effectiveness.